Wavelet based OFDM with V-BLAST Virtual MIMO for Wireless Multimedia Sensor Networks - Rafique, Zimran (Auckland University of Technology, 2014)
Wireless sensor networks (WSNs) are finding their place in many real life applications because low power and small-size sensor nodes can be inexpensively and easily deployed in the areas of interest for different applications. Wireless multimedia sensor networks (WMSNs) consist of wireless nodes capable of producing multimedia (image/video) data streams that will enable a new generation of WSN applications. The transmission of multimedia content involves high volume data communication that may require significant bandwidth and energy resources. Hence, supporting high data rate while maintaining energy efficiency is a key challenge of WMSNs. Multi-Input Multi-Output (MIMO) techniques can be used to increase the data rate for a given bit error rate (BER) and transmission power. Due to the small form factor, energy and processing constraints of WSN nodes, sometimes it is not feasible to equip the nodes with multiple antennas. Virtual MIMO as opposed to True MIMO system architecture is considered more feasible for WSN applications. In this thesis, we analyse the performance of WSN with Virtual MIMO system architecture at transmitter side, and True or Virtual MIMO system architecture using Vertical Bell Laboratories Layered Space Time (V-BLAST) signal processing technique at receiver side. We investigated for the first time, the impact of different modulation techniques on the performance of a Virtual MIMO system based on V-BLAST architecture with multi-carrier modulation techniques in the context of WMSNs. Through analytical models and simulations using real hardware and environment settings, both communication and processing energy consumptions, BER, spectral efficiency, and total time delay performances have been analysed. The results show that Virtual MIMO system with Binary Phase Shift Keying-Wavelet based Orthogonal Frequency Division Multiplexing (BPSK-WOFDM) modulation is a promising solution for future high data-rate and energy-efficient WMSNs. This research also proposes a new channel equalisation technique which uses Quadrature Mirror Filter (QMF) bank architecture that is also found in WOFDM modulator and demodulator. The proposed technique is found to perform better in terms of BER, energy efficiency, and total time delay as compared to QR detection process. In this thesis, we also present a novel method to mitigate the problem of phase offset, which is a major issue affecting the performance of Virtual MIMO systems. We optimise the wavelet bases of BPSK-WOFDM technique using genetic algorithm (GA) to compensate for unwanted phase differences between sensor nodes in a Virtual MIMO WSN. Results show that the optimised BPSK-WOFDM technique can effectively mitigate the phase offset issue.
Keywords: Wireless Multimedia Sensor Networks; Virtual MIMO; Wavelet based OFDM; V-BLAST